Investigating the impact of monsoon season on the dispersion of pollutants emitted from vehicles: A case study of Salalah City, Sultanate of Oman. (March 2018) - Charabi, Yassine; Abdul-Wahab, Sabah; Al-Rawas, Ghazi; Al-Wardy, Malik; Fadlallah, Sulaiman
Graphical abstract: Highlights: The dispersion of pollutants emitted from vehicles during monsoon season in Salalah was investigated. CALPUFF simulation model was utilized on selected days for modeling both monsoon and non-monsoon seasons. The results revealed that levels of pollutants during the monsoon season were greater than those of the non-monsoon season. Abstract: The paper concentrates on utilizing CALPUFF to model and investigate the impact of the monsoon season on the dispersion of carbon monoxide (CO), carbon dioxide (CO2 ), and nitrogen oxides (NOx ) emitted from vehicles. During monsoon season, traffic jams have become an important issue in Salalah, Oman, due to a rapid increase in visitors to Salalah at that time of the year. Therefore, the main aim of the current work is to evaluate the region's concentrations of CO, CO2, and NOx during monsoon season and compare them with non-monsoon season levels. The CALPUFF simulation analysis was based on selected modeling days for both monsoon and non-monsoon seasons. The modeling periods' meteorological conditions were multifarious. Thus, as a result, concentration levels, as well as the coordinates where concentrations exceeded the criterion limits, differed. Seasonal comparisons revealed that concentration levels of CO, CO2, and NOx during the monsoon season were greater than the levels associated with the modeling days during the non-monsoon season.